2019
DOI: 10.3389/fpsyg.2019.01904
|View full text |Cite
|
Sign up to set email alerts
|

Mental Control in Musical Imagery: A Dual Component Model

Abstract: Hearing music in your head is a ubiquitous experience, but the role mental control plays in these experiences has not been deeply addressed. In this conceptual analysis, a dual-component model of mental control in musical imagery experiences is developed and discussed. The first component, initiation, refers to whether the musical imagery experience began voluntarily or involuntarily. The second component, management, refers to instances of control that occur after the experience has begun (e.g., changing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
0
17
0
Order By: Relevance
“…Hearing music in the head appears to be a ubiquitous experience (Cotter, 2019) but the role that mental control or effort plays in these experiences has not been addressed in current research in any thorough manner. That is, both professional musicians and music writers, as well as musically naïve individuals, have the power to start, stop, shape, and maintain in their head musical images unfolding in time (e.g., Zatorre, 1999;Janata, 2001;Cotter, 2019). However, all these mental ''actions'' are a form of cognitive work and require focused attention; they are likely to draw on mental resources and engage brain systems the control cognitive arousal (Alnaes et al, 2014).…”
Section: Musical "Audiation"mentioning
confidence: 99%
“…Hearing music in the head appears to be a ubiquitous experience (Cotter, 2019) but the role that mental control or effort plays in these experiences has not been addressed in current research in any thorough manner. That is, both professional musicians and music writers, as well as musically naïve individuals, have the power to start, stop, shape, and maintain in their head musical images unfolding in time (e.g., Zatorre, 1999;Janata, 2001;Cotter, 2019). However, all these mental ''actions'' are a form of cognitive work and require focused attention; they are likely to draw on mental resources and engage brain systems the control cognitive arousal (Alnaes et al, 2014).…”
Section: Musical "Audiation"mentioning
confidence: 99%
“…People generally did not strongly endorse these items, implying that management failure is not the norm. When asked whether they felt their imagery was under their control, Cotter et al (2019) found that students generally perceive a moderate level of control over their imagery. Further, reported that, when asked to change specific elements of their musical imagery in daily life (e.g., tempo, vocalist's gender), both music and nonmusic students report being able to do so most of the time and do not perceive managing their imagery to be difficult.…”
Section: Ecological Musical Imagerymentioning
confidence: 99%
“…How people exercise mental control over inner musical experience appears complex and remains poorly understood. Traditionally, musical imagery has been labeled as voluntary or involuntary without consideration of the variety of ways in which people can exercise control over these internal experiences (see Cotter, 2019; Williams, 2015). A recent framework suggests that mental control of musical imagery can be thought of in two ways (see Cotter, 2019, for review)—initiation and management.…”
mentioning
confidence: 99%
“…Musical imagery is multi-faceted ( Cotter, 2019 ). This study did not assess whether musical imagery is broken down into general imagination processes and imagery specific to music.…”
Section: Discussionmentioning
confidence: 99%